# 1

HYPERBOLIC, INVERSE HYPERBOLIC & INVERSE TRIGONOMETRIC FUNCTIONS
1.1: COMPREHEND HYPERBOLIC FUNCTIONS 1.1.1: Define Hyperbolic Functions   Combinations of exponential functions (ex) Form of: sinh, cosh, tanh, cosech, sech and coth

1.1.2: Calculate Values of Hyperbolic Functions

FORMULA:
    

Example (a) Find the value of: i. sinh (1.275) ii. cosh (2.156) iii. tanh (ln 3) Solution: i. sinh (1.275)

Step 1: Identify the formula

sinh x 

e x  ex 2

Step 2: Replace the value of x into the formula → sinh 1.275 

x = 1.275

e1.275  e1.275 2

= 1.65

1

ii.

cosh (2.156)

cosh x 

e x  ex 2

cosh 2.156 

e2.156  e2.156 = 4.376 2

iii.

tanh (ln 3)

tanh x 

e x  ex e x  e x eln 3  e ln 3 eln 3  eln 3
= 0.8

tanh(ln 3) 

Try this!

Find to 4 decimal places for: a) b) c) d) cosech (-2.5) sech (-ln 2) coth (0.38)

1.1.3: Sketch Graphs of Hyperbolic Functions HYPERBOLIC FUNCTIONS GRAPH HYPERBOLIC FUNCTIONS GRAPH

sinh

cosech

cosh

sech

tanh

coth

2

Example (b) Sketch the graph of Solution:

y = cosh x from point

x = -5

to

x=5

Step 1: Create table from start point to end point (using calculator) x y -5 74 -3 10 0 1 3 10 5 74

Step 2: Sketch graph by referring to the table

74

10

-5

-3

3

5

Try this!

a) b)

A curve line is based on Fill in the table below using x y 2.5

. If c = 50, Calculate the value of y when x = 109. . Then sketch a graph. 2.9 3.3 3.7 4.1 4.5

1.1.4: Prove Identities of Hyperbolic Functions

FORMULA:
     

Example (c) Prove that: i. 2 sinh (x + y) cosh (x – y) = sinh 2x + sinh 2y ii. cosh x – sinh x = e-x iii. 1 – tanh2 x = sech2 x 3

Solution: i. 2 sinh (x + y) cosh (x – y) = sinh 2x + sinh 2y

Step 1: Expand the equation based on formula.

2 sinh (x + y) cosh (x – y)

= (

)(

)

Step 2: Simplify the calculations until proven.

2 sinh (x + y) cosh (x – y)

= = =( ) ( ) = sinh

2x + sinh 2y

ii.

cosh x – sinh x = e-x =( = = =e
-x

)

(

)

iii. 1 – tanh2 x

= sech2 x = = = =( =(
( (

(
) (

)
) ) ( ( ) )

)

)

= sech

2

x

Try this!

Verify that: a) b) c) sinh2 x – sinh2 y = cosh2 x – cosh2 y cosh 2x = 1 + 2 sinh2 x coth 1 𝑥 = ln (
1 𝑥 1 𝑥 1

)

x y

2.5

2.9

3.3

3.7

4.1

4.5

4